The Effectiveness of the Cybernetic Approach in Learning Management on Student Creativity and Learning Responsibility at SMKN 1 Sawoo - Sofa, Yanna; Widiayanti, Rina; Vika Shelayanti, Vika; Manan, Samiro; Nasrullah, Muhammad; Yusuf, Arief Rahman (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the effectiveness of implementing a cybernetic approach in learning management in developing students’ creativity and responsibility for learning at SMKN 1 Sawoo. Using a qualitative phenomenological approach, the study explores the experiences and meanings constructed by teachers, students, and school administrators regarding the application of the cybernetic approach in the learning process. Data were collected through in-depth interviews, participant observation, and documentation, with participants selected purposively. The data were analyzed cyclically using an interactive analysis model. The findings show that the implementation of a cybernetic approach in learning management contributes to a more planned, controlled, and sustainable learning process, accompanied by more intensive teacher–student interaction. This approach positively influences students’ creativity, as reflected in their ability to generate ideas, think innovatively, and produce varied learning outcomes. In addition, students’ responsibility for learning improves, as indicated by increased discipline, independence, and commitment to completing learning tasks. These results suggest that the cybernetic approach has the potential to support more adaptive and meaningful learning management in vocational education contexts.